Application of Concurrent Engineering for G.O.L.D.S Constellation as a Cyber-Physical System-of-Systems - Souto, Moisés Cirilo de Brito; Silva, Lucas Rafael Leandro; Zotovici, Andréa; Martins, Larissa; Mattiello-Francisco, Maria De Fátima; Loureiro, Geilson (Anais do Workshop on Validation and Verification of Future Cyber-physical Systems (WAFERS), 2022)
The paper’s objective is to describe the application of concurrent engineering to propose a mission control architecture for an open constellation of educational satellites for collecting environmental data. This research methodology considers the knowledge gained from exploratory research carried out through systems engineering case studies to develop artifacts for mission operational concepts. The case study demonstrates a structured analytical approach to the Global Open Collection Data System (G.O.L.D.S), presenting analytical and operational considerations early in the product and organizational lifecycle. The system of systems conceived features the characteristics of the cyber-physical domain, including various activities in different organizations and systems to deliver the desired outcomes. The proposed architecture derives from a concurrent engineering process and facilitates the exchange of services between a multi-segment shared infrastructure (space, ground, and data collection stations) through Application Programming Interfaces (APIs) and users.